SYSTEMATIC APPROACH TO ORGANIZING THE ACCOUNTING OF COSTS OF A LOGISTICS COMPANY - ROZHKO, Viktor; KOVALENKO, Vitalii (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article analyzes the methods of cost accounting and the possibility of testing them for logistics companies. A number of cost accounting methods are presented and the possibility of their use is substantiated taking into account the specifics of the activities of logistics companies. Attention is focused on the fact that a harmonious combination of cost accounting methods is an important condition for the effectiveness of a logistics company. The concept of a systematic approach to organizing the cost accounting of a logistics company is formed and the key principles of the systematic approach are specified. The main categories of costs of a logistics company are defined and their essence is formed. It is proven that optimization of cost processes is an important aspect of achieving the goals of a logistics company. This helps to increase the efficiency of internal operations, reduce costs, improve competitiveness in the market and ensure sustainable profitability growth. Optimization of cost processes allows for more efficient use of the company’s resources, reduces service costs, which leads to an increase in overall business efficiency. It is noted that involving personnel in cost management is the most important aspect for any company. When employees understand how their actions affect the company’s financial performance, they become more knowledgeable and responsible. This can lead to a decrease in unnecessary costs, an increase in productivity and, finally, an increase in the company’s overall profit. It is also important to consider that satisfied staff who feel important to the company are usually more efficient and loyal. Therefore, involving staff in cost management can have a positive impact on all aspects of a logistics company. It has been proven that the use of modern technologies in cost accounting systems is crucial to improving the efficiency of a company. Using technologies such as cloud computing, data analytics and automation, companies can optimize cost accounting processes, improve the accuracy of cost tracking, identify cost savings opportunities and make data-based decisions. In general, the concept of a systematic approach to organizing cost accounting for a logistics company helps to achieve the set goals and ensure the successful development of a logistics company. The possibility of ensuring that accounting fulfills its role in reflecting costs is analyzed. In particular, additional sub-accounts are proposed to account for the expenses of a logistics company.